In search of the Burdigalian GSSP. New evidence from the Contessa Section (Italy) - Fabbrini A; Baldassini N; Caricchi C; Foresi LM; Sagnotti L; Dinarès-Turell J; Di Stefano A; Lirer F; Menichetti M; Winkler A; Di Stefano S (Italian Journal of Geosciences, 2019)
The Contessa Section is a reference section for the early Miocene in the Mediterranean. Along this 36 m thick section 115 samples were collected and analysed for an integrated bio-magnetostratigraphic study through the Scaglia Cinerea and Bisciaro formations. Planktonic foraminifera were analysed semi-quantitatively, while calcareous nannofossils were examined using the standard quantitative method. A reliable biozonation for both fossil groups was then accomplished. The paleomagnetic analyses identified a sequence of magnetozones, then correlated with the ATNTS using the calcareous plankton bioevents. The investigated interval extends from foraminiferal Zone P22 (Chattian) to MMi2c (Burdigalian) and from calcareous nannofossils Zone MNP25a to MNN3a, thus from Chron C7An to C5En. Therefore, the section chronologically spans from 24.80 Ma to 18.10 Ma. Three hiatuses were recognised along the section: H1 at 0.63 m from the base (comprising a minimum time interval from 24.36 Ma to 23.38 Ma), H2 at 12.33 m (between 21.80 Ma and 21.35 Ma) and H3 at 34.03 (between 19.21 Ma and 18.40 Ma). All three hiatuses were correlated with regional megahiatuses identified in the North Atlantic Ocean and in the Paratethys area. Furthermore, the First Occurrence of the calcareous nannofossil Helicosphera ampliaperta is recognised within Chron C6An.2n at 19.77 m from the base (6 m above the volcaniclastic Raffaello Level). This event provisionally defines the Aquitanian/Burdigalian boundary according to the literature. Thus, the Contessa Section is a possible candidate for the definition of the Burdigalian Global Stratigraphic Section and Point. Finally, the age of the Raffaello Level (a regional marker horizon for the early Miocene) is discussed in this new integrated stratigraphic framework, falling in Chron C6AAn and dated between 21.09 Ma and 21.08 Ma